Extended Linear and Nonlinear Lorentz Transformations and Superluminality - Dara Faroughy (Advances in High Energy Physics)
Two broad scenarios for extended linear Lorentz transformations (ELTs) are modeled in Section 2 for mixing subluminal and superluminal sectors resulting in standard or deformed energy-momentum dispersions. The first scenario is elucidated in the context of four diverse realizations of a continuous function